PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS CANVA DALAM MENUNJANG PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN DASAR-DASAR MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS - Salsabila Putri, Najwa; Faslah, Roni; Riyantie, Mayang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The E-Module constitutes an innovation in digital instructional materials designed to enhance learning interactivity while facilitating differentiated instruction in accordance with students' readiness, interests, and learning styles. This study analyzes the developmental process, evaluates the feasibility, and examines the effectiveness of a Canva-based Interactive E-Module developed for the Fundamentals of Office Management and Business Services course among Grade X MPLB students at SMK Negeri 62 Jakarta. A Research and Development (R&D) approach was adopted, employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) as its developmental framework. Validation involved three experts specializing in content, instructional design, and media, complemented by empirical trials conducted through small-group and large-group testing. The content expert validation yielded a score of 96.25% (Very Feasible), the instructional design expert validation produced 78.33% (Feasible), and the media expert validation attained 92.86% (Very Feasible). The small-group trial recorded a feasibility percentage of 86.20% (Very Feasible), with mean scores increasing from 69.29 in the pre-test to 87.14 in the post-test. Similarly, the large-group trial produced a feasibility percentage of 88.00% (Very Feasible), with mean scores rising from 67.95 to 86.64. These findings demonstrate that the Canva-based Interactive E-Module is both feasible and effective as an independent instructional resource, capable of enhancing students' comprehension and learning outcomes. Moreover, students' favorable responses indicate the module's potential to foster learning motivation, reinforcing its contribution to the effective implementation of differentiated learning.